Epipsammic Diatoms of Sülük Lake (Ağın/Elazığ, Türkiye) - Caglar, Metın (My University, 2025)
In this study, epipsammic diatoms in water sampled from a particular station on Sülük Lake (Ağın/Elazığ) between March-November 2022 were examined. A total of 36 taxa belong to the epipsammic diatoms were identified throughout the investigation. Nitzschia was dominant with 5 taxa, followed by Cymbella and Surirella with 4 taxa. When the water temperature started to rise in the spring and summer, the diatoms reached the highest number. In the summer, water temperature (23.10 °C), dissolved oxygen (8.5 mg/L), and electrical conductivity (331.1 mho/cm) were recorded higher than others. The Sülük Lake is vulnerable to eutrophication because of its coastal structure, small surface area and especially useing as a picnic place in the spring and summer.
Keywords: Diatom; Sülük Lake; Epipsammic